Discrimination of Biodiesel-Diesel of B7 and B10 by Infrared Spectroscopy with Dendogram - Mohd Rashidi Abdull Manap; Ahmad Fadly Jusoh; Lim Xiang Chuin; Nur Diana Farhana Muhamad Zulkifli; Qhurratul Aina Kholili; Fatin Abu Hasan; Danish Aiman Akmal Mohd Effendy; Ramizah Azis (Universitas Gadjah Mada, 2023)
Spectroscopists face an ongoing challenge in identifying fuel spectra due to a wide range of fuel formulations and the increasing abuse of biodiesel-diesel blends. In Malaysia, a new type of biodiesel-diesel blend known as B7 and B10 has been introduced, which requires rapid and reliable discrimination methods. However, current identification methods are costly and time-consuming. To overcome this issue, a spectroscopy study was conducted using a portable Fourier transform infrared (FTIR) spectrometer to identify biodiesel-diesel blends. The study found that direct identification using spectral libraries was reliable in identifying complex samples but unable to differentiate B7 and B10 due to the libraries' focus on hydrocarbons rather than esters. Instead, FTIR spectroscopy provided unique spectral peaks for each blend. Spectral range influences the discrimination, and the truncated region 1697–1777 and 1164–1224 cm−1 was shown to be reliable for discriminating the B7 and B10. The study concluded that a combination of algorithms, libraries, and hierarchical cluster analysis (HCA) in FTIR spectroscopy could effectively differentiate the blends. The primary objective was to differentiate B7 and B10 by analyzing liquid samples collected in Malaysia using HCA and IR spectroscopies. FTIR spectroscopy provides molecular-specific vibrational signals and is proven as a rapid identification method.